The Effect of Quality and Price on Satisfaction and Impact on Consumer Loyalty - Indra Setiawan; Saiful Hendra; Kuwat Suroto; Andie Setiyawan; Ahmad Mico Wahono (Universitas Medan Area, 2022)
Quality can be referred to as the characteristics of a product or service that depend on its contribution to satisfying consumer expectations. Quality is very closely related to consumers, namely quality provides an impetus to consumers to establish a strong relationship with the company. FMCG is a wet tissue manufacturer. During the Covid-19 pandemic, the company's customers experienced a drastic decline. The purpose of the study was to analyze the effect of quality and price on consumer satisfaction and its impact on consumer loyalty. This research uses Path Analysis method. Sampling was carried out by 100 respondents using wet tissue. The results showed that the quality and price directly have a significant effect on consumer satisfaction. Directly, customer satisfaction has a significant effect on consumer loyalty. This means that the greater the customer satisfaction, the greater the customer loyalty. Quality and price, it has no significant effect on consumer loyalty without going through customer satisfaction, while quality and price have a significant effect on customer loyalty if through customer satisfaction